From affection cities to the healthy cities - Hirao, Helio (Saúde e Sociedade, 2020)
Experiments of thinking the production of subjectivities in the city through the affects between the bodies (human, architectural and territorial) to enhance of human well-being with improvement of public health. The World Health Organization points to health as “a state of complete physical, mental and social well-being and not just the absence of illness and disease.” This paper seeks to investigate healthy cities relating as a built and social environment with city subjects focusing on the multiple and complex health particularities in transformation and movement. Therefore, this study deals with three experience orientations developed with final undergraduate works in Architecture and Urbanism, using a rhizomatic methodological approach of Deleuze and Guattari, with the practice of situationist derive and experimentation of affections cartographies, to strengthen interventions in the side of rivers in Bragança Paulista and Presidente Prudente cities. Thus, through the process of the production of affects in the intensities zones, multiplicities, heterogeneities and singularities of space allowed to vibrate all who approached to engage in a libertarian spatial proposal in the microspaces of resistance, activating them, promoting social invisibilities and, in this way, empower the healthy city.